Hubungan Pola Makan Dengan Status Gizi Pada Anak Kelas V Di SDN Warung Lega 01 Kecamatan Cikancung Kabupaten Bandung - Deni Arisandi; Reni Rohimah (Pusat Riset dan Inovasi Nasional, 2021)
Elementary school children aged around 7-13 years are the second most rapid growth period after toddlerhood. UKS data from SDN Warung Lega 01 in January, the results of a preliminary study on class V children, showed that 3 students were overnourished, 14 students had normal nutrition, 22 students were undernourished, and 1 student was malnourished. To find out about eating patterns, to find out nutritional status, to find out whether there is a relationship between eating patterns and children's nutritional status. Using a correlational descriptive method with a cross sectional approach. Sampling was carried out with a total sampling of 40 respondents. Data analysis in this study used bivariate techniques with rank spearmen. The spearmen rank test results were 0.058 > α (0.05) so Ho was rejected and Ha was accepted. This research shows that there is no relationship between eating patterns and the nutritional status of students at SDN Warung Lega 01. Description of eating patterns. More than half (57%) of respondents have a pattern of eat well, namely 23 respondents. Description of nutritional status More than half (55%) of respondents had poor nutritional status, namely 22 respondents. Relationship between diet and nutritional status. From the calculation results, a significance value of 0.058 > α is obtained, so the working hypothesis Ha is rejected, meaning that there is no relationship between diet and nutritional status. There is no significant relationship between eating patterns and the nutritional status of class V students at SDN Warung Lega 01